A study of the seismic response modification factor for log shear walls - Kessler, Samantha (Kansas State University, 2010)
Log construction is becoming increasingly popular throughout the U.S. Currently, seismic coefficients are not provided in model building codes for the design of the log shear walls as a lateral force resisting system for seismic forces. Current design practice is to use a response modification coefficient, R, of around 4.5. Several tests by other researchers on log shear walls showed strong energy dissipation and good lateral strength with stability after high displacements. This behavior of the log shear wall system is evidence that a higher R could possibly be used in design. The purpose of this study was to establish a response modification factor for single story log shear walls based on available shear wall tests using the definition of R provided in ATC-19. This research did not conduct testing according to the protocol and methodology of ATC-63. This work contains a history of the development of seismic design provisions in the U.S. and the evolution of the response modification coefficient. Common log construction practices are reviewed, with reference to ICC 400- Standard on Design and Construction of Log Structures. Using data provided by other researchers from physical testing and computer modeling of various types of log shear walls, an R of 6.0 is proposed based on the provisions of ATC-19. Finally, recommendations for further research to fully understand the behavior of the log shear wall system, including possible archetypes required by the methodology set forth in ATC-63, are provided.
Keywords: Log Shear Wall; Seismic; Lateral Behavior; Response Modification Coefficient; Architecture (0729); Engineering, Civil (0543)